Bayesian Method Applied to Decision Making in Neurology — Methodological Considerations - Salamon, R.; Bernadet, M.; Samson, M.; Derouesne, C.; Gremy, F. (Methods of Information in Medicine, 1976)
This article presents an analysis of the method used in an experiment in computer-aided diagnosis, applied to the whole field of neurology.While the method is based on the classical Theorem of Bayes, it nevertheless contains a number of new elements:— By means of a self-learning procedure, it makes use of the patient sample as it grows in size;— there is an overall analysis of results as well as an individual analysis of each diagnosis.
Keywords: Computer-aided Diagnosis; Self-learning Process; Bayes’ Theorem; Evaluation of a Decision Process